Tolerance and Pluralism Between Religious People in the Film Kos-Kosan - Arya Andryan Dimas Prasetya; Vani Dias Adiprabowo (Jurnal Penelitian Sosial Ilmu Komunikasi, 2024)
This study examines the values of tolerance between religious communities as reflected in the short film "Kos-Kosan" by Paniradya Kaistimewan. This research was carried out to explore the representation of tolerance in everyday life, reflecting the social and cultural conditions of Indonesian society in accepting religious differences and encouraging socio-religious inclusion. The research method used is descriptive qualitative. Namely, the researcher describes in depth what was obtained from observations about the film. This research aims to determine the harmony between explicit and implicit meaning in the narrative, dialogue, and scenes in the short film "Kos-Kosan" with three indicators. This study underlines the critical role of films in reflecting and promoting the values of inter-religious tolerance and pluralism. The content analysis shows that films from various genres and cultures can be a powerful medium for strengthening inclusive messages about respecting religious differences and working together across religions.